1987
DOI: 10.1021/ie00062a002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cetane number by group additivity and carbon-13 Nuclear Magnetic Resonance

Abstract: Cetane number is a measure of ignition quality, specifically ignition delay, of diesel fuel. It is an engine measure of a kinetic phenomena. While it is typically inappropriate to use a thermodynamic measure, such as molecular structure, to predict kinetic behavior, molecular structure does correlate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“…The cetane numbers for both the butene oligomer mixtures and the dimerized 2‐ethyl‐1‐hexene mixtures have not yet been determined. However, a calculation utilizing a simple additive method for a hydrogenated butene trimer suggests that mixed oligomer fuels will have moderate cetane numbers (>35) 55. This may allow for these mixtures to act as standalone diesel fuels or blending agents with other butanol derived fuels such as dibutyl ether.…”
Section: Saturated Hydrocarbon Fuels From Butanolmentioning
confidence: 99%
“…The cetane numbers for both the butene oligomer mixtures and the dimerized 2‐ethyl‐1‐hexene mixtures have not yet been determined. However, a calculation utilizing a simple additive method for a hydrogenated butene trimer suggests that mixed oligomer fuels will have moderate cetane numbers (>35) 55. This may allow for these mixtures to act as standalone diesel fuels or blending agents with other butanol derived fuels such as dibutyl ether.…”
Section: Saturated Hydrocarbon Fuels From Butanolmentioning
confidence: 99%
“…Many empirical relationships between the aromaticity and CN of diesel fuels have been reported elsewhere [27,28]. On the basis of such correlations, the increase in CN of LCO was determined from the change in aromaticity (f a ).…”
Section: Temp °Cmentioning
confidence: 99%
“…Prior models based on quantitative structure property relationships (QSPR) have been developed to predict the CN of different compounds, which included an early, but limited, application of backpropagating neural networks for predicting the CN of isoparaffins and diesel fuels [5]. Though the study was limited to branched paraffins, the model showed a superior predictive power compared to conventional equations [6]. A subsequent study used quantitative structure property relationship (QSPR) software to generate 100 molecular descriptors for a set of 275 compounds, including 147 hydrocarbons and 128 oxygenates [7]; a genetic algorithm, or a search heuristic mimicking natural selection in regards to optimization problems, was used to identify which descriptors might influence CN.…”
Section: Predicting the Cetane Numbermentioning
confidence: 99%
“…This is due to the fact that many of the values for some parameters are equal for the majority of molecules, which is detrimental to the neural network and unhelpful in capturing the nonlinear behavior. Historically, 14-23 descriptors have been chosen for similar approaches in the literature [5][6][7]11]. The process is repeatable across multiple attempts, which suggests that the chosen set is likely to be the most influential descriptors in regards to CN prediction for this database.…”
Section: Neural Network Architecturementioning
confidence: 99%